2015
DOI: 10.1007/s13132-015-0343-7
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Mission Statements in Italian Universities: Results of an Empirical Investigation on Strategic Orientation

Abstract: "This paper explores the strategic orientation of Italian universities with a special focus on their vision and mission statements. It has been possible to collect data for 89 universities, by means of a survey sent by e-mail to all 95 Italian universities and by visiting all their websites. [...] Results are mixed and show that one sub-group of Italian universities is very pro-active and innovative in its strategic planning; another sub-group interprets strategic planning as nothing more than a legal complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…Lillisa and Lynch (2014) adopted a documentary analysis approach, based on strategic plans and institutional review reports, combined with interviews with senior managers in charge of strategic planning, to define the current situation about strategic planning in the Irish education system. In Italy, Giusepponi and Tavoletti (2015) studied the strategic orientation of higher education institutions by conducting interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lillisa and Lynch (2014) adopted a documentary analysis approach, based on strategic plans and institutional review reports, combined with interviews with senior managers in charge of strategic planning, to define the current situation about strategic planning in the Irish education system. In Italy, Giusepponi and Tavoletti (2015) studied the strategic orientation of higher education institutions by conducting interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Then, fewer studies on this topic have been carried out about the Irish context (Lillisa and Lynch, 2014), the Ukrainian one (Hladchenko, 2016) and the Spanish one (Palomeras Montero et al , 2012). In Italy, universities’ official declarations are not yet completely investigated, because of the recent introduction of strategic planning in higher education, and the only studies about their content are by Giusepponi and Tavoletti (2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Saichaie and Morphew (, p. 512), for example, found that the ‘beauty, size, and scope’ of campuses were regularly showcased through images of their most attractive areas, such as iconic buildings or quads (also see Hartley and Morphew, , p. 679, for similar findings). Research also finds that academic rigour is touted through the announcement of prestigious academic awards, grants and fellowships acquired by institutional members (Harris, ; Pizarro Milian and Davidson, ), as well as espoused through mission statements which cite institutional ambitions to conduct world‐class research (James and Huisman, ; Kuenssberg, ; Creamer and Ghoston, ; Giusepponi and Tavoletti, ). Rigour is often complemented within promotional materials with what Tobolowsky and Lowery () term as notions of a ‘rich’ life, consisting of a more holistic and enriching experience—including athletics and other social activities (also see Hite and Yearwood, ; Clayton et al ., ; Davidson, ).…”
Section: Marketing In Higher Educationmentioning
confidence: 99%
“…A number of studies on entrepreneurship have emerged from European countries (Linan et al, 2011;Nowiński and Haddoud, 2019;Yurtkoru et al, 2014), South American countries (Krauss Delorme et al, 2018;Krakauer et al, 2018;Torres et al, 2017) and the USA (Kadir et al, 2012;Al-Shammari and Waleed, 2018;Ambad and Damit, 2016). Some studies report that universities located in more developed countries tend to have been more entrepreneurial in recent years (Åstebro et al, 2012;Giusepponi and Tavoletti, 2018;Lopes, Antunes and Rodrigues, 2018).…”
Section: Introductionmentioning
confidence: 99%